2020
DOI: 10.1101/2020.04.28.066845
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tumor invasion as non-equilibrium phase separation

Abstract: TWO-SENTENCE SUMMARY: Using a multicellular spheroid embedded within an engineered threedimensional matrix, we show here the potential for coexistence of solid-like, fluid-like, and gas-like phases of the cellular collective described by a jamming phase diagram. Depending upon cell type and matrix density, moreover, invasion into matrix from the tumor periphery can switch from a continuous cellular collective that flows like a fluid to discrete cells that scatter individually like a gas. ASTRACT:The early mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 89 publications
(146 reference statements)
2
24
0
Order By: Relevance
“…We performed t-SNE on data generated using simulations of an expanding tumor spheroid model 15,18,29,30 . The results revealed massive dynamical heterogeneity that depends on the radial distance from the tumor center, which accords well with the conclusions in recent experiments [11][12][13] . t-SNE also resolves the dynamical phase space structure of cells in the core and periphery.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…We performed t-SNE on data generated using simulations of an expanding tumor spheroid model 15,18,29,30 . The results revealed massive dynamical heterogeneity that depends on the radial distance from the tumor center, which accords well with the conclusions in recent experiments [11][12][13] . t-SNE also resolves the dynamical phase space structure of cells in the core and periphery.…”
supporting
confidence: 91%
“…Previously we showed that the cell dynamics in a growing multicellular spheroid (MCS) is spatially heterogeneous 15,18 , which implies that cells in the core (periphery) exhibit sub-diffusive (super-diffusive) motion. These characteristics were first observed in imaging experiments tracking the displacement of cells moving in a collagen matrix, and recently in other studies as well 12,13 . However, characterizing the dynamics using conventional ensemble average measures, such as mean squared displacement or the self-intermediate scattering function, hide the rich dynamics, the cause of DITH.…”
mentioning
confidence: 56%
See 3 more Smart Citations